The anabolic response to plant-based protein ingestion - Pinckaers, P. J. M.; Trommelen, J.; Snijders, T.; van Loon, L. J. C. (Sports Medicine, 2022)
There is a global trend of an increased interest in plant-based diets. This includes an increase in the consumption of plant-based proteins at the expense of animal-based proteins. Plant-derived proteins are now also frequently applied in sports nutrition. So far, we have learned that the ingestion of plant-derived proteins, such as soy and wheat protein, result in lower post-prandial muscle protein synthesis responses when compared with the ingestion of an equivalent amount of animal-based protein. The lesser anabolic properties of plant-based versus animal-derived proteins may be attributed to differences in their protein digestion and amino acid absorption kinetics, as well as to differences in amino acid composition between these protein sources. Most plant-based proteins have a low essential amino acid content and are often deficient in one or more specific amino acids, such as lysine and methionine. However, there are large differences in amino acid composition between various plant-derived proteins or plant-based protein sources. So far, only a few studies have directly compared the muscle protein synthetic response following the ingestion of a plant-derived protein versus a high(er) quality animal-derived protein. The proposed lower anabolic properties of plant- versus animal-derived proteins may be compensated for by (i) consuming a greater amount of the plant-derived protein or plant-based protein source to compensate for the lesser quality; (ii) using specific blends of plant-based proteins to create a more balanced amino acid profile; (iii) fortifying the plant-based protein (source) with the specific free amino acid(s) that is (are) deficient. Clinical studies are warranted to assess the anabolic properties of the various plant-derived proteins and their protein sources in vivo in humans and to identify the factors that may or may not compromise the capacity to stimulate post-prandial muscle protein synthesis rates. Such work is needed to determine whether the transition towards a more plant-based diet is accompanied by a transition towards greater dietary protein intake requirements.